Challenges in applying the GRADE approach in public health guidelines and systematic reviews: a concept article from the GRADE Public Health Group - Hilton Boon, Michele; Thomson, Hilary; Shaw, Beth; Akl, Elie A; Lhachimi, Stefan K; López-Alcalde, Jesús; Klugar, Miloslav; Choi, Leslie; Saz-Parkinson, Zuleika; Mustafa, Reem A; Langendam, Miranda W; Crane, Olivia; et al. (Journal of clinical epidemiology, 2021)
BACKGROUND AND OBJECTIVE: This article explores the need for conceptual advances and practical guidance in the application of the GRADE approach within public health contexts. METHODS: We convened an expert workshop and conducted a scoping review to identify challenges experienced by GRADE users in public health contexts. We developed this concept article through thematic analysis and an iterative process of consultation and discussion conducted with members electronically and at three GRADE Working Group meetings. RESULTS: Five priority issues can pose challenges for public health guideline developers and systematic reviewers when applying GRADE: (1) incorporating the perspectives of diverse stakeholders; (2) selecting and prioritizing health and "nonhealth" outcomes; (3) interpreting outcomes and identifying a threshold for decision-making; (4) assessing certainty of evidence from diverse sources, including nonrandomized studies; and (5) addressing implications for decision makers, including concerns about conditional recommendations. We illustrate these challenges with examples from public health guidelines and systematic reviews, identifying gaps where conceptual advances may facilitate the consistent application or further development of the methodology and provide solutions. CONCLUSION: The GRADE Public Health Group will respond to these challenges with solutions that are coherent with existing guidance and can be consistently implemented across public health decision-making contexts.
Keywords: směrnice jako téma; Public Health; veřejné zdravotnictví; lidé; Guidelines as Topic; Systematic Reviews as Topic; systém GRADE; Evidence-Based Medicine; medicína založená na důkazech; GRADE Approach; systematický přehled jako téma; Humans